Truncated NTRK2 is induced in CAP1 endothelial cells during mouse lung injury-repair - Celine Shuet Lin Kong; Mitheera V; Jezreel Pantaleón-García; Scott E. Evans; Jichao Chen (iScience, 2025)
Summary: Pulmonary capillary endothelial cells (ECs) consist of two populations, CAP1 and CAP2; how each population reacts to diverse tissue injury is incompletely understood. Using single-cell multiome and mouse genetics, we characterize the induction and function of a truncated isoform of Ntrk2, Ntrk2-T1, in multiple lung injury models. Upon Sendai parainfluenza infection, Ntrk2-T1 is broadly induced in CAP1s after the initial interferon response, associated with increased intronic chromatin accessibility, and persists for weeks. Ntrk2-T1 ECs arise from CAP1s but not CAP2s—traced by KitCreER and Car4CreER, respectively—and proliferate and give rise to CAP1s but not CAP2s, as traced by Ntrk2CreER. Although also induced by lipopolysaccharide, H3N2 influenza, and COVID-19 injuries, EC-specific deletion of Ntrk2 has limited molecular and cellular consequences. Individuals with incident and prevalent respiratory diseases have lower plasma NTRK2. Our data identifies Ntrk2-T1 as an EC marker of lung injury-repair and enhances our understanding of EC heterogeneity.